Increased Demand for Therapeutic Drugs in Pediatric Ulcerative Colitis Patients With Extraintestinal Manifestations - Kwon, Yiyoung; Kim, Eun Sil; Choe, Yon Ho; Kim, Mi Jin (Frontiers in Pediatrics, 2022)
Background Ulcerative colitis (UC) is a systemic inflammatory disease with a gut predominance, which may involve other organs. The presence of extraintestinal manifestation (EIM) is an important symptom for clinicians as it alters the treatment decisions. In this study, we aimed to evaluate the initial clinical presentation and disease severity of pediatric UC patients with EIMs. Methods One hundred forty-two patients under the age of 18 years who were diagnosed with UC from January 2003 to November 2021 were included in this study. Forty-seven patients with confirmed EIMs and 95 patients without EIMs were divided into two groups and their differences were analyzed. Results The most common EIM was peripheral arthritis. The disease extent at the time of diagnosis shows a higher rate of pancolitis in the EIM-positive group (65.9%) than that of the EIM-negative group (33.7%) (p < 0.001). More than 90% of EIM-positive patients had moderate to severe disease activity on the Mayo endoscopic subscore. In the EIM-positive group, the cumulative use of systemic steroids, immunosuppressants, and biological agents from diagnosis to 1 year follow-up were significantly higher than those of the EIM-negative group (p = 0.009, 0.001, and < 0.001, respectively). About 80% of patients in the EIM-negative group reached remission, but only about 50% of the EIM-positive patients reached remission (p = 0.005). The relapse occurred more frequently in the EIM-positive group than in the EIM-negative group with statistical significance (p < 0.001). Conclusion Pediatric UC with EIMs had higher disease severity and often manifested upper gastrointestinal tract involvement. Despite EIMs treatment, the occurrence of new EIMs was observed repeatedly. Cumulative drug demand (steroids, immunosuppressants, and biological agents) for the treatment increased steadily over time, and frequent relapses occurred despite the combinatory use of therapeutic drugs.